Biodiversity reporting: Comparing listed entities in the United Kingdom and South Africa - Dino Da Mata; Timothy Lai; Dusan Ecim; Warren Maroun; Dannielle Cerbone (South African Journal of Business Management)
Purpose: This research conducts an analysis of biodiversity reporting among a sample of companies listed on the stock exchanges of South Africa (SA) and the United Kingdom (UK). The aim is to present empirical evidence on how organisations address and report on biodiversity-related matters to their stakeholders and investors.